Windows server 2008 Hyper-V unleashed - Morimoto, Rand (Sams, 2009)
Using the Hyper-V virtualization capabilities built into Windows Server 2008, organizations can slash costs for power, space, and maintenance, and dramatically improve IT flexibility at the same time. This is the first book to offer comprehensive, independent, real-world coverage of planning, designing, implementing, and supporting Windows Server 2008 Hyper-V virtualization environments. Authored by Rand Morimoto and Jeff Guillet-top consultants of Microsoft technologies with unsurpassed experience deploying Hyper-V in enterprise organizations-this book delivers start-to-finish guidance for every facet of your virtualization initiative. Leverage the experience from hundreds of real world implementations of Hyper-V and Virtual Machine Manager 2008 in your deployment of a virtualized server environment Implement best practices for planning, prototyping, and deploying Hyper-V-including strategies, processes, and templates Install and configure Windows 2008 Server with Windows Hyper-V Services Provide guest operating systems ranging from Windows 2003 Server to Linux Administer Hyper-V Host Servers as standalone hosts or in multiple host environments Optimize Hyper-V Host Server and guest sessions, by efficiently allocating memory, processors, disk space, and other resources Move from basic server virtualization to a systematically managed virtual enterprise environment Use Virtual Machine Manager 2008 to centrally monitor all your Hyper-V hosts and guest sessions Quickly provision new guest images wherever and whenever you need them Implement reliable failover processes to overcome failures in guest sessions, host systems, or sites Troubleshoot problems with both Hyper-V hosts and guest operating systems.
Print version record
Keywords: Microsoft Windows server Hyper-V; Virtual computer systems; Systèmes virtuels (Informatique)